Sound and silence in the poetry of Keats - Davies, Sarah E. (My University, 1902)
Introduction: In reading the poetry of Keats for the first time, I was much impressed by the many passages expressive of sound which he brings into his poems. The instances of silence are also numerous and very significant. Through his entire work we find over three-hundred expressions indicating sound, and over seventy passages expressing a lack of sound. Keats was undoubtedly, most exquisitely sensitive to the beauty of the things of sense; for his poems show that things from without appealed to him much more strongly than any promptings from within. It seems his ear was ever open to the melody of sound, for in his poems we find many passages bringing to our minds the melodious strains of musical instruments, and the cheering songs of birds. Even the bleating of sheep, the lowing of cattle, and the characteristic sounds of other animals, undoubtedly found a responsive chord in the heart of the poet. He felt beauty also in the sighing of the wind, in the rippling of waters, and in the voices of human beings. He does not however, confine himself to pleasing sounds alone, and we are sure that such sounds as the roar of wild beasts, sighs and groans of human beings and the howling of tempests, also touched him.
Citation: Davies, Sarah E. Sound and silence in the poetry of Keats. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Keats; Poetry; Literature; English; Theses; Manuscripts (documents)